National antibiotic consumption is strongly related to the prevalence of antibiotic resistance across bacterial clades - Stilianos Louca (iScience)
Summary: The impact of societal antibiotic consumption on the prevalence of antibiotic resistance across microbial taxa in natural environments has not yet been assessed at global scales. Here, I examine the prevalence of 155 antibiotic resistance genes (ARGs) in 300,209 bacterial genomes, from non-clinical non-human-associated terrestrial environments at over 9,600 locations in 44 countries. I then compare ARG prevalences to nationwide antibiotic consumption rates, distinguishing between different ARG types. I find that depending on country and ARG type, ARG prevalences can be extremely high; for example, the probability that a given quinolone resistance gene is present in a given strain in Thailand was estimated at 42%. Further, I find strong positive correlations between nationwide antibiotic consumption rates and mean ARG prevalences for nearly all ARG types. Thus, national antibiotic consumption leaves a signal on the prevalence of ARGs across the bacterial tree, even in non-clinical environments.